PENGARUH LAMA PERENDAMAN DAN CARA PENGERINGAN TERHADAP MUTU LADA PUTIH - Sri Usmiati dan Nanan Nurdjannah (Jurnal Teknologi Industri Pertanian, 2006)
Abstract. The quality of white pepper at farm level is relatively low, sometimes it doesn’t meet the quality needed by  importer. White pepper processing technology to improve the quality of white pepper at farm level have been produced, which consist of the processing technology and its equipments. The aim of the study was to get the best of soaking time and drying method at farm level which is suitable in respect to processing method and meet the International quality standard for pepper from International Pepper Community (IPC). 100 kg of pepper berries from 8-9 months age was used for each combination treatment. The study was designed as randomized Block Designed, with two replications, and replication I and II are used as the block. The treatments applied consist of: (A) soaking period: 6 (A1), 7 (A2) and 8 (A3) days, and (B) drying methods: improved sunlight method (B1), and mechanical drying at 45-60oC (B2). White pepper produced by farmers from Batuah village, Kutai Kartanegara District, East Kalimantan Province where the study was conducted was used as control. Parameters observed were color, essential oil content, light berries content, extraneous matter, black berries content, and microbe content (TPC, fungi/yeast, Coliform and Salmonella spp). The result showed that the quality of white pepper produced by improved processing technology was better than the one produced by traditional method. White pepper produced has brighter color, oil content is higher than the ISO standard/R 959 (2.3-3.1%), water content is less than IPC WP-1 standard (10.4-12.3%), TPC less than IPC is standard (1.75x102-3.48x103 CFU/g) and free from Salmonella contamination.Key words: technology, processing, white pepper